Management of Rice Field Through Water Arrangements to Improve Rice Production - Wahid Erawan (Lembaga Sembilan Tiga Community, 2020)
Efforts to achieve an increase in rice field processing programs in increasing agricultural production. However, there are many various kinds of obstacles that we must face. Farmers say their land has been planted with rice so far but often fails to harvest because, in the dry season, it is often drought, and in the rainy season, it is often flooded. To meet the consumption needs of farm families is only enough for daily needs. The purpose of this study is to study the benefits of managing paddy fields by regulating irrigation to increase rice production. Data is taken from experience in Banjar, South Kalimantan. The results show that the use of irrigation is more appropriate for planting 2 to 3 times. It is expected that the printing of paddy fields in the irrigation can be carried out as quickly as possible and run well and smoothly without any obstacles. Thus farmers can enjoy the results with two harvests in a year. To be more supportive of various aspects, related parties can provide various kinds of training and direction so that paddy fields can increase their productivity. At present, far, the expected results.